Studies on the Variability in Biochemical Characters in F1 Progenies of Peach (Prunus persica L.) - DEVI, Y. INDRANI; ROY, S. S. (Indian Journal of Hill Farming, 2014)
Peach (Prunus persica L.) is an important fruit crop valued for its fresh and canned forms. There are a large number of cultivars, which are grown in different agro-climatic conditions in states like Jammu and Kashmir, Himachal Pradesh and North Eastern States. In the present study, some hybrids, evolved from crosses using six female parents (July Elberta, Alton, J. H. Hale, Kanto-5, Saharanpuri and Quetta) and one male parent (Kateroo, a local peach cultivar of Himachal Pradesh), were evaluated for some important biochemical parameters. The fruits harvested from these hybrids were evaluated in terms of titrable acidity, total soluble solid, reducing sugar, non-reducing sugar, total sugar andTSS/acid ratio. The mean values for titrable acidity for each cross varied between 0.50 to 0.75%, TSS from 11.53 to 12.90oB, reducing sugars from 2.33 to 2.88%, non-reducing sugars from 6.27 to 6.83%, total sugars from 9.24 to 10.05% and TSS/acid ratio between 14.47 to 23.90. The coefficient ofvariability varied from 11.07 to 31.50% for titratable acidity, 0.00 to 23.02% for TSS, 5.24 to 18.53% for reducing sugars, 2.09 to 15.14% for non-reducing sugars, 0.00 to 6.80% for total sugars and 18.23 to 156.51% for the TSS/acid ratio in these crosses. Significant variation with respect to biochemicalparameters observed in different cross combinations showed the vast scope for improvement of this important fruit crop.